The Relationship among Pre-Service EFL Teachers’ Beliefs about Language Learning, Pedagogical Beliefs, and Beliefs about ICT Integration - Inayati, Dian; Emaliana, Ive (IAIN Samarinda, 2017)
This paper elucidates the relationship among pre-service teachers’ beliefs about language learning, pedagogical beliefs, and beliefs about ICT Integration through survey methodology. This study employed a quantitative approach, particularly a correlational relationship to investigate the relationships among beliefs about language learning, pedagogical beliefs, and beliefs about ICT integration by utilizing structural equation modeling (SEM). SEM was applied to model the relationships in a set of three domains: beliefs about language learning, pedagogical beliefs, and beliefs about ICT integration. A questionnaire was administered to 103 pre-service EFL teachers who have accomplished their teaching practice in secondary schools. The results of the three types of beliefs obtained from the questionnaire were then analyzed through Structural Equation Model (SEM). It was revealed that there was a significant positive relationship between beliefs about language learning and pedagogical beliefs, and that between the former and beliefs about ICT integration, while a positive correlation between pedagogical beliefs and beliefs about ICT integration was not found. Insightful implications to EFL teaching and learning were discussed.